CONTRIBUIÇÕES DOS PROCESSOS PEDAGÓGICOS NA FORMAÇÃO DOS DOCENTES DE EDUCAÇÃO FÍSICA - Oliveira, Ricardo de Campos (2011)
This research has as objective to analyze the pedagogical historical process of the Physical Education, the national guidelines of the degree courses and the Physical Education and the course curriculum for Physical Education contextualizing the curricular matrices of three courses of the region of the Great São Paulo ABC in this panorama and finally to argue concerning these questions and to stimulate reflections and quarrels of this subject among the professionals and researchers of the area. For in such a way we made documental research of the description historical-pedagogical processes why it passed the area of the Physical Education, the trends of its constitution as area of studies, the basic legislation that gave sustentation to it, the crisis of identity of the area and the division, degree course and bachelor´s degree. The theories of the course curriculum had given sustentation to the analysis that we´ve made.